Pemanfaatan Ikan Gabus Sebagai Upaya Pencegahan Stunting - Andriansyah, Aan Afit; Qomar, Akhmad Nazri Nurul; Dzururoh, Kharismatu; Zahroh, Lia Amelia Fatimatuz; Sholikhah, Lifa Nur Aminatus (ISEI Cabang Pekanbaru, Koordinator Provinsi Riau, 2023)
The snakehead fish population (family Channidae) is widespread in the fresh waters of Indonesia. Snakehead fish is a native fish in Sumatra, Java, and Kalimantan but is an introduced fish in Sulawesi and Papua. Channa striata, or snakehead fish, is a freshwater fish that has many health benefits, especially its albumin content for wound healing. Other types of freshwater fish that are suspected of having potential for albumin, besides snakehead fish, are toman fish (Channa micropeltes) and betutu fish (Oxyeotris marmorata). Snakehead fish are also very suitable for treating stunting that occurs in children. Stunting is a developmental disorder experienced by children due to malnutrition, repeated infections, and inadequate psychosocial stimulation. Several factors cause stunting, namely the practice of giving colostrum and exclusive breastfeeding, children's consumption patterns, and infectious diseases. Stunting is a disease that currently exists in Paregan village; for this reason, Paregan village residents must pay attention to their children's diet. Parengan village is one of the villages in the Maduran sub-district, Lamongan district, which is close to the Bengawan Solo bank. The distance between Bengawan Solo and the village is approximately 60 m, limited by 2 blocks. Parengan village has 16 RTs and 04 RWs. Parengan village is a village with a narrow land area of around 62 ha, so the majority are woven craftsmen, and only ± 20 people make a living as farmers.